TRANS-ISOMERIZED FATTY ACIDS IN HYDROGENATED FATS (American Journal of Technology and Applied Sciences, 2023)
The article outlines ways to improve the quality and ensure the food safety of fats obtained by hydrogenation of cottonseed oil, through the selection of scientifically based highly effective technologies and catalytic systems that allow reducing the content of trans-isomerized fatty acids and regulating the necessary arrangement of fatty acids in triacyl glycerides of edible fats.